Electric field processing: novel perspectives on allergenicity of milk proteins - Pereira, Ricardo N. (2018)
Milk proteins are being widely used in formulated foods due to their excellent technological, functional and biological properties. However, the most representative proteins from casein and whey fractions are also recognized as major allergens and responsible for the prevalence of cows milk protein allergy (CMPA) in childhood. Electroheating technologies based on thermal processing of food due to application of moderate electric fields, also known by Ohmic Heating or Joule effect, are establishing a solid foothold in food industry. Currently, the influence of OH on allergenic aspects of milk proteins is under debate but still undisclosed. The occurrence of electrical effects in protein structure and its function has already been reported, thus the impact of OH over allergenicity should not be overlooked. Based on these recent findings it is then relevant to speculate about the impact of this emergent technology on the potential allergenicity of milk proteins.